URINATION AS A CASE OF HAGEN-POISEUILLE FLOW - BAPPAH, MUHAMMAD AHMADU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2019)
The flow of urine in the human urethra is modeled as a natural voluntary flow of incompressible Newtonian fluid in a cylindrical flow tract (tube or pipe-like), with a view to test the suitability of Hagn-Poiseulles flow theory to natural flow of fluids in human body. With the assumption of the cylindrical nature of the urethra and the voluntary nature of urine pumping, the urethral model is tried. The resultant flow quantities in terms of the axial flow velocity, volume flux, and generated axial pressure gradient, as obtained by solving the modified Navier-Stokes equations, in particular the flow speed, tend to agree with some experimental figures obtained in earlier studies. This shows the possible application of this type of flow to similar physiological situations.